2018
DOI: 10.1051/0004-6361/201730671
|View full text |Cite
|
Sign up to set email alerts
|

TFAW: Wavelet-based signal reconstruction to reduce photometric noise in time-domain surveys

Abstract: Context. There have been many efforts to correct systematic effects in astronomical light curves to improve the detection and characterization of planetary transits and astrophysical variability. Algorithms like the Trend Filtering Algorithm (TFA) use simultaneouslyobserved stars to measure and remove systematic effects, and binning is used to reduce high-frequency random noise. Aims. We present TFAW, a wavelet-based modified version of TFA. TFAW aims first, to increase the periodic signal detection and second… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The light curves were denoised using wavelet denoising technique before modeling to decorrelate the patterns of variability common to all the stars in the frame but uncorrelated in time (del Ser et al 2018). Also, to take care of the noise pattern unique to the host stars and correlated in time caused by stellar activity or pulsation etc.,we have adopted Gaussian process correlated noise modeling technique during modeling to model its covariance structure and to take it into account when calculating the likelihood of the data given the model (Johnson et al 2015;Barclay et al 2015).…”
Section: Data Reduction Analysis and Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The light curves were denoised using wavelet denoising technique before modeling to decorrelate the patterns of variability common to all the stars in the frame but uncorrelated in time (del Ser et al 2018). Also, to take care of the noise pattern unique to the host stars and correlated in time caused by stellar activity or pulsation etc.,we have adopted Gaussian process correlated noise modeling technique during modeling to model its covariance structure and to take it into account when calculating the likelihood of the data given the model (Johnson et al 2015;Barclay et al 2015).…”
Section: Data Reduction Analysis and Modelingmentioning
confidence: 99%
“…Wavelets have already been used extensively in the light curve noise analysis and filtering (Cubillos et al 2017;Waldmann 2014). In case of transit photometry, wavelet denoising can efficiently remove the outliers, yield better MCMC posterior distributions and reduce the bias in the fitted transit parameters and their uncertainties (del Ser et al 2018). We used the pywt package (Lee et al 2018) and followed the same procedure as described in del Ser et al (2018).…”
Section: Treatment Of Noisementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, instead of smoothing the light curves with some low-pass filter, we used a more robust technique, namely the Wavelet Denoising (Donoho & Johnstone 1994;Quan Pan et al 1999;Luo & Zhang 2012). Although wavelet based denoising techniques have been widely used in image processing and remote sensing in various fields of science and engineering, it is a recent addition in the context of transit photometry and other light curve analysis (e.g., del Ser et al 2018;Cubillos et al 2017;Waldmann 2014). CS19 applied this technique on the light curves obtained from their observational data and demonstrated that this technique produces no distortion in the transit light curves, but yields better MCMC posterior distributions for the fitted transit parameters.…”
Section: Wavelet Denoisingmentioning
confidence: 99%
“…Most of the pre-processing techniques (such as binning and Gaussian smoothing) that can reduce the effect of these timeuncorrelated noise components also tend to distort the shape of the transit signal. CS19 have demonstrated that the Wavelet Denoising technique (Donoho & Johnstone 1994;Quan Pan et al 1999;Luo & Zhang 2012;del Ser et al 2018;Cubillos et al 2017;Waldmann 2014) can be used to reduce the time-uncorrelated fluctuations in the light-curves without distorting the transit signal and improves the precision of the estimated physical parameters (see Table 3 and Table 4 of CS19) to a great extent. Wavelet denoising technique also reduces the outliers in the light-curves due to cosmic ray events.…”
Section: Introductionmentioning
confidence: 99%